PAPILLARY THYROID CARCINOMA PRESENTING AS A BENIGN ECTOPIC THYROID MASS IN THE ANTERIOR MEDIASTINUM: A CASE REPORT - David, Mary Lourdes Grace; Narvacan-Montano, Carolyn; Abalos, Alyanna; Cedeño, Joseph Ray Richard (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE An incidental papillary thyroid carcinoma (PTC) presenting as a mediastinal mass with benign ectopic thyroid cells is a rare occurrence. We present a case of a 33-year-old Filipino female who presented with sudden onset difficulty of breathing and chest heaviness. On workup, she was found to have an anterior mediastinal mass, which showed ectopic thyroid cells on biopsy. Thyroid ultrasound revealed a 1.25x 1 x 1.13 cm nodule on the thyroid gland which showed suspicious for PTC on fine needle aspiration biopsy. The patient underwent total thyroidectomy and excision of the anterior mediastinal mass. The histopathologic report of the thyroid mass revealed a conventional unifocal PTC, while the excised tissues comprising the mediastinal mass were consistent with benign ectopic thyroid tissues with colloid goiter. Since thyroid cancer is considered as lowrisk, suppression therapy and active surveillance is the choice of management for this unusual case.